Secagem em camada de espuma (Foam-mat drying) da folha do noni (Morinda citrifolia L.) - Lima, Anna Caroline Feitosa (2020)
Species Morinda citrifolia L., from Rubiaceae family, popularly known as noni, although widely consumed in Asia for more than 2000 years, is still unknown in Brazil. Phytochemical studies show that noni leaves contain a variety of chemical components, including terpenoids, phytosterols, fatty acids, glycosidic iridoids, glycoside flavonoids, among others. Drying is a way to increase the shelf life of products, since by reducing water activity, the risk of proliferation of microorganisms is reduced. Among the types of drying, there is the drying in foam layer, which among several benefits is the low cost. The aim of this research was to evaluate the drying in the foam layer noni leaf to obtain its powder form. The foaming agent used was Portogel®, previously defined in preliminary tests, and the foam obtained was physically characterized in terms of stability, density and over run. The drying was carried out according to the complete factorial design of 2³ + 3 central points, with independent variables: concentration of foaming agent (3, 4 and 5%), stirring time (3, 4 and 5 minutes) and temperature drying time (50, 60 and 70 ° C) in order to verify their influence on drying time and final dry base moisture. The drying and drying rate curves showed typical behavior, characterized by a long constant period followed by a short period of decreasing rate. The highest drying rates were shown in the experiments at 70 ° C and the lowest rates at 50 ° C. The powder obtained in the eleven experiments showed average humidity values of approximately 5.07% (b.u.) and water activity of 0.288, which favors conservation and commercialization within the standards required by legislation. The other physico-chemical characterizations of the powder (yield, solubility, total soluble solids, total titratable acidity, pH, lipid content, ascorbic acid content and ash) presented values close to those found in literature for other types of powdered leaves as well as for the powdered noni fruit. The influence of addition of the foaming agent was analyzed through the lyophilized powder for the analysis of total soluble solids, pH and total titratable acidity, whose comparison with the values of the eleven experiments did not show significant changes. The best conditions found for large-scale manufacturing are those of experiment 5 (3%, 3min, 70 ° C), since it uses a low concentration of the foaming agent, it presented the second shortest drying time (140 minutes), and the shortest water activity (aw), which minimizes the chances of microbiological contamination and allows greater storage safety.